A GHRHR founder mutation causes isolated growth hormone deficiency type IV in a consanguineous Pakistani family - Ahmad, Safeer; Ali, Muhammad Zeeshan; Abbasi, Sumra Wajid; Abbas, Safdar; Ahmed, Iftikhar; Abbas, Shakil; Nawaz, Shoaib; Ziab, Mubarak; Ahmed, Ikhlak; Fakhro, Khalid A.; Khan, Muzammil Ahmad; Akil, Ammira Al-Shabeeb (Frontiers in Endocrinology, 2023)
Background Isolated growth hormone deficiency (IGHD) in children is characterized by growth and developmental failure due to disruption of the growth hormone (GH) or growth hormone releasing hormone (GHRHR). Patients with IGHD type IV have short stature, reduced serum GH levels, and delayed bone age. Objectives To identify the causative mutation of IGHD by genetic mapping of a consanguineous family of four affected by IGHD4 (MIM#618157) and exploration of its functional impact using in silico approaches. Methods Clinical and radiological studies were performed to determine phenotypic spectrum and hormonal profile of the disease. Whole exome sequencing (WES) and Sanger sequencing were performed to identify the disease-causing mutation. In silico studies involved protein structural modeling and docking, and molecular dynamic simulation analyses using computational tools. Parallel to this, the data from Qatar Genome Program (QGP) was also screened for the presence of founder variant and its associated phenotypic effect in the Qatari population. Result All affected individuals presented short stature, without any gross skeletal anomalies, and a significant reduction in serum GH levels. Genetic mapping revealed a homozygous nonsense mutation [NM_000823:c.G214T:p.(Glu72*)] in the third exon of the GHRHR gene (MIM#139191). The identified variant segregated in all patients, but was absent in the normal individuals. The substituted amber codon (UAG) presumably truncates the protein by deleting the C-terminus GPCR domain. Protein modeling studies have shown drastic effect of this mutation on GHRHR structure and its interaction with GHRH, and thus confirms its involvement in disease etiology. Conclusion: We provide evidence of a p.Glu72* as a founder mutation of GHRHR that disrupts the receptor, affects the hormonal signaling and causes IGHD type IV. Our in silico and biochemical analyses support the pathogenic effect of the reported nonsense mutation. Moreover, our comprehensive phenotype analysis, and hormonal profiling will help in establishing the genotype-phenotype correlation.